2004
DOI: 10.4049/jimmunol.173.7.4297
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor-Specific Long-Term Immunity of Hemaggluttinating Virus of Japan-Mediated Dendritic Cell-Tumor Fused Cell Vaccination by Coadministration with CpG Oligodeoxynucleotides

Abstract: Immunization with dendritic cells (DCs) using various Ag-loading approaches has shown promising results in tumor-specific immunotherapy and immunoprevention. Fused cells (FCs) that are generated from DCs and tumor cells are one of effective cancer vaccines because both known and unknown tumor Ags are presented on the FCs and recognized by T cells. In this study, we attempted to augment antitumor immunity by the combination of DC-tumor FC vaccination with immunostimulatory oligodeoxynucleotides containing CpG m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
(74 reference statements)
1
38
0
Order By: Relevance
“…Ag presentation by DCs, in the absence of proper costimulation, induces tolerance (1). In particular, recent studies suggest that TLR-agonist CpG ODNs or conserved pathogen-associated molecular patterns, such as OK-432, start the DC maturation process, which is a critical event in the induction of full effector function in T cells (20,31,32,35,41,57,58). Therefore, we next investigated whether DCs activated by a combination of TLR ligation and up-regulated HSPs enhance the immunogenicity of FCs.…”
Section: Discussionmentioning
confidence: 99%
“…Ag presentation by DCs, in the absence of proper costimulation, induces tolerance (1). In particular, recent studies suggest that TLR-agonist CpG ODNs or conserved pathogen-associated molecular patterns, such as OK-432, start the DC maturation process, which is a critical event in the induction of full effector function in T cells (20,31,32,35,41,57,58). Therefore, we next investigated whether DCs activated by a combination of TLR ligation and up-regulated HSPs enhance the immunogenicity of FCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that DCs treated by SeV secrete several inflammatory cytokines, including IL-1␤, IL-6, and TNF-␣, that are strong activators to DCs in mixture (33); however, no knowledge of how DCs exposed to SeV express these cytokines is available at present. A recent important report indicated that DCs treated with SeV produce multiple proinflammatory cytokines independent of TLRs and their adaptors, including MyD88 (34), unlike LPS, CpG (35), or OK-432 (36), which stimulate DCs through a TLR-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Murine dendritic cells derived from bone marrow were generated as described from BALB/c mice (12). Briefly, bone marrow of the tibia and femur was flushed with culture medium and then the effluent was filtered through a 40-mesh sieve.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HVJ-E has been applied to an anticancer vaccine strategy (11,12). We previously showed that HVJ-E can incorporate and possibly deliver anticancer drugs (13).…”
Section: Introductionmentioning
confidence: 99%